2017
DOI: 10.1159/000475709
|View full text |Cite
|
Sign up to set email alerts
|

Late-Onset Inflammatory Bowel Disease-Like Syndrome after Ipilimumab Therapy: A Case Report

Abstract: Background: Antitumor immunotherapy has become a major player in cancer therapy. Ipilimumab is a humanized monoclonal antibody against the cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), an important downregulator of T-cell activation. Ipilimumab has demonstrated tumor regression and improvement in overall survival in patients with metastatic melanoma. Unfortunately, immune activation induced by this drug has been associated with several immune-mediated adverse effects, namely diarrhea and colitis. Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 8 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…This adverse condition usually presents as a triad of diarrhea, abdominal pain, and vomiting (227). Enterocolitis is particularly frequent and severe following CTLA-4 inhibition, and appears to resemble, and even cause inflammatory bowel diseases (228,229). In the above-mentioned report utilizing anti-CTLA-4 antibodies, Faecalibacterium genus and other Firmicutes not only correlated with a good treatment outcome, but also with the frequency and severity of enterocolitis (223).…”
Section: Microbiome and Tumor Immunitymentioning
confidence: 90%
“…This adverse condition usually presents as a triad of diarrhea, abdominal pain, and vomiting (227). Enterocolitis is particularly frequent and severe following CTLA-4 inhibition, and appears to resemble, and even cause inflammatory bowel diseases (228,229). In the above-mentioned report utilizing anti-CTLA-4 antibodies, Faecalibacterium genus and other Firmicutes not only correlated with a good treatment outcome, but also with the frequency and severity of enterocolitis (223).…”
Section: Microbiome and Tumor Immunitymentioning
confidence: 90%
“…In the majority of patients the rectum or/and the left colon are involved therefore the flexible sigmoidoscopy is sufficient for diagnosis. However some patients need colonoscopy [22][23][24]. The endoscopic lesions include erythrema, luminal bleeding, erosions and ulcerations [22][23][24].…”
Section: Gastroenterological Toxicities Induced By Immunotherapymentioning
confidence: 99%
“…However some patients need colonoscopy [22][23][24]. The endoscopic lesions include erythrema, luminal bleeding, erosions and ulcerations [22][23][24]. The presence of these changes but also a normal appearance of the mucosa are usually not sufficient.…”
Section: Gastroenterological Toxicities Induced By Immunotherapymentioning
confidence: 99%
“…Immunological studies on the biopsy material from patients with ipilimumab-associated colitis revealed abundance of plasma cells and CD4+ T cells in the lamina propria by immunohistochemistry as well as increased expression of interferon-γ and IL17A mRNA by reverse transcriptase polymerase chain reaction (RT-PCR) [ 52 ]. Rare cases of late-onset IBD-like syndrome developing 3 years after ipilimumab therapy have been reported [ 56 ].…”
Section: Anti-tumoral Agentsmentioning
confidence: 99%